Biochemical characterization of PEPC from cassava: a preliminary report - López F., Y.; Vélez, W.; El-Sharkawy, Mabrouk A.; Mayer, Jorge Edgard (International Center for Tropical Agriculture, 1993)
We want to understand the physiological mechanisms underlying the high photosynthetic rates of cassava under drought stress and high temperatures. Histological analysis of leaf cross sections with cassava PEPC specific antiserum to establish the enzymic compartmentalization pattem is our next goal. Phosphoenolpyruvate carboxylase (PEPC) from cassava has been purified to>95 purity by liquid chromatography (fractionated ammonium sulphate precipitation, desalting by Sephadex G-25, DEAE Sepharose ion exchange, and gel filtration through Sephacryl S-300 HR). One peak of activity was eluted from DEAE Sepharose by salt gradient at 0.125 M ammonium sulphate. Gel filtration yielded two peaks of 350 and 400 kDa, respectively. Specific activity of the main peak was 5.5 units/mg protein. PEPC activities from maize, beans, and cassava leaves were compared using a spectrophotometric assay and Fast Violet detection on polyacrylamide gels. PEPC relative content and activity in cassava have intermediate values between maize and beans. A maize PEPC specific antiserum cross-reacts with cassava PEPC, indicating homologous antigenic determinants. This has also been shown at the DNA level in hybridization studies with a maize ppc probe and total, enzyme digested cassava genomic DNA. The production of a specific antiserum will enable the conduction of histological analysis of PEPC within photosynthetic tissues using immunofluorescence techniques.